The Therapeutic Potential of Galectin-3 in the Treatment of Intrahepatic Cholangiocarcinoma Patients and Those Compromised With COVID-19 - Li, Hao; Li, Jianmin; Xiao, Wei; Zhang, Yujing; Lv, Yuan; Yu, Xing; Zheng, Jiao (Frontiers in Molecular Biosciences, 2021)
The novel coronavirus pneumonia COVID-19 is characterized by all age susceptibility, which imposes a dramatic threat to the human species all over the world. According to current available data, the cytokine storm appears to be the most life-threatening symptom of severe COVID-19 cases accompanied with lung fibrosis. Galectin-3 (Gal-3), a member of soluble β-galactoside-binding lectin families, has been implicated as a key regulator in various inflammation conditions in addition to its well-documented roles in cancer. The pro-inflammatory activity of Gal-3 in the inflammatory response and lung fibrosis of COVID-19 has been proposed by emerging studies, which suggested that inhibition of Gal-3 may represent a novel treatment approach for COVID-19 patients. Intrahepatic cholangiocarcinoma (ICC) is an aggressive malignancy with poor prognosis. ICC accounts for 10-25% of primary liver cancers with limited therapeutic options, which has higher incidence in Asian countries, particularly in China. Cancer patients, including ICC patients, are highly vulnerable to COVID-19 due to their impaired immune system. It is thus undoubtedly a challenge for our oncology department to establish effective treatment strategies under the influence of the COVID-19 crisis. According to our management procedures in the COVID-19 era, emergency treatment will be applied to ICC patients who are under life-threatening conditions, despite the COVID-19 infection. To the best of our knowledge, the modulatory function of Gal-3 in ICC is still barely explored to date. In order to evaluate the therapeutic potential of Gal-3 for ICC patients or those comprised with COVID-19, we herein report our preliminary investigation into roles of Gal-3 in ICC. Our results exhibited that the expression of Gal-3 was significantly up-regulated in ICC tissues, and a significant correlation was observed between its overexpression and malignant progression of ICC cells. We further discussed the activity and possible molecular mechanisms of Gal-3 in ICC, which may pave the ways for further exploring the possibility of Gal-3 as a potential therapeutic target for treating ICC patients or those with COVID-19-related conditions.